2019
DOI: 10.1007/s11938-019-00231-8
|View full text |Cite
|
Sign up to set email alerts
|

Diet as Adjunctive Treatment for Inflammatory Bowel Disease: Review and Update of the Latest Literature

Abstract: Purpose of review Diet plays an integral role in development of inflammatory bowel disease (IBD) and continues to act as a mediator of intestinal inflammation once disease sets in. Most clinicians provide little dietary guidance to IBD patients, in part due to lack of knowledge in nutrition and lack of available nutritional resources. The purpose of this review is to provide clinicians with a brief summary of the latest evidence behind diets popular among IBD patients; to highlight diets with known efficacy; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 45 publications
0
48
0
3
Order By: Relevance
“…A recent meta-analysis concluded that an LFD is effective in reducing GI symptoms in patients with quiescent IBD. However, this does not seem to be due to a further improvement in intestinal inflammation, because no differences in fecal calprotectin were found between IBD patients on a LFD in comparison with those on a standard diet [56,57].…”
Section: Lfd Beyond Ibsmentioning
confidence: 93%
See 1 more Smart Citation
“…A recent meta-analysis concluded that an LFD is effective in reducing GI symptoms in patients with quiescent IBD. However, this does not seem to be due to a further improvement in intestinal inflammation, because no differences in fecal calprotectin were found between IBD patients on a LFD in comparison with those on a standard diet [56,57].…”
Section: Lfd Beyond Ibsmentioning
confidence: 93%
“…Finally, given the proven efficacy of the LFD diet within the context of functional gastrointestinal symptoms, it is still necessary to broaden the field of study to other diseases that often have some symptoms in common with IBS and which could probably benefit from an LFD. These include IBD, functional esophageal and duodenal disorders, exercise-related gastrointestinal symptoms, radiation-induced enteropathy and nonceliac gluten sensitivity [55,57,[96][97][98][99][100].…”
Section: Hopes For the Futurementioning
confidence: 99%
“…Najnowsze badania wykazały, że wyłączne żywienie dojelitowe pozostaje najskuteczniejszą metodą wywołania remisji w aktywnej chorobie Crohna. Badania pokazują, że może być ono skuteczne nawet w zamykaniu przetok jelitowo-skórnych w ciężkiej postaci ChLC [24]. Ponadto wykazano zależność między modyfikacją diety polegającą na kilkutygodniowej fazie eliminacji niektórych pokarmów, po której następowała faza podtrzymująca, a poprawą jakości życia związaną z większą częstością remisji w NChZJ.…”
Section: Znaczenie Diety Eliminacyjnej I żYwienia Dojelitowegounclassified
“…Among patients with IBD, a dietary approach that has gained traction is the specific carbohydrate diet (SCD), which consists of consuming monosaccharides at the exclusion of polysaccharides and disaccharides (excluding sucrose and certain starches). In general, grains, table sugar, and food preservatives are disallowed, while fruits, some vegetables, nuts, meats, and eggs are mostly permitted . The rationale for the SCD is that fermentation of complex carbohydrates in the colon results in malabsorption, diarrhea, and bacterial overgrowth .…”
Section: Therapeutic Potential Of Microbial Alterationmentioning
confidence: 99%
“…In general, grains, table sugar, and food preservatives are disallowed, while fruits, some vegetables, nuts, meats, and eggs are mostly permitted. 154 The rationale for the SCD is that fermentation of complex carbohydrates in the colon results in malabsorption, diarrhea, and bacterial overgrowth. 155 Interestingly, this is mutually exclusive to the dietary approach proposed above that involved complex carbohydrates to stimulate the growth of bacteria responsible for SCFA production.…”
Section: Dietary Therapymentioning
confidence: 99%